Archibald Campbell and the Committee for Purity of Doctrine on Natural Reason, Natural Religion, and Revelation. Issue 2 (17th February 2016) - Maurer, Christian
Summary: This article discusses Archibald Campbell's (1691–1756) early writings on religion, and the reactions they provoked from conservative orthodox Presbyterians. Purportedly against the Deist Matthew Tindal, Campbell crucially argued for two claims, namely (i) for the reality of immutable moral laws of nature, and (ii) for the incapacity of natural reason, or the light of nature, to discover the fundamental truths of religion, in particular the existence and perfections of God, and the immortality of the soul. In an episode that had its peak in 1735 and 1736, a Committee for Purity of Doctrine of the Church of Scotland scrutinised Campbell's writings. It attacked the second claim as contradicting Calvinist doctrines concerning the universal guilt of mankind after the Fall, and the first claim as contradicting doctrines concerning justification and salvation, and as supporting Deism. The study of this episode reveals new aspects of how the struggle to define orthodoxy crystallised in philosophical and theological debates in Scotland at the dawn of the Enlightenment, and before the rise of the Moderates.